Temperatures in high efficiency deep grinding - Bell, Andrew John (Cranfield University, 2009)
This research considers the temperatures generated in the workpiece during profile and cylindrical traverse grinding in the High Efficiency Deep Grinding (HEDG) regime. The HEDG regime takes large depths of cut at high wheel and workpiece speeds to create a highly efficient material removal process. This aggressive processing generates high temperatures in the contact zone between the wheel and workpiece. However, the beneficial contact angle and the rapid removal of the heated wheel – workpiece contact zone results in low temperatures in the finished surface. Temperatures in the ground surface can be predicted with knowledge of the specific grinding energy and the grinding parameters used. Specific grinding energies recorded at high specific material removal rates demonstrated a constant value of specific grinding energy dependent on cutting and contact conditions, improving accuracy of the predictive model. This was combined with a new approach to burn threshold modelling, which demonstrated an improved division of damaged and undamaged surfaces. Cutting and contact conditions in the grinding profile vary dependent on their position. This thesis shows how temperatures vary with location and estimates the partitioning of the heat flux to the regions of the grinding profile. This suggested a constant partitioning of energy to each of the three surfaces considered independently of specific material removal rates. Further a potential link was shown between the surface and the sidewall of the grinding profile, which allows temperatures in a secondary surface to be predicted given knowledge of that in the primary. Finally, the work has demonstrated the feasibility of the Superabrasive Turning process. Using small values of feed per turn and high workpiece feedrates promoted high values of removal rate with low depths of thermal penetration in the as ground surface. Thus the process has become viable for high speed cylindrical traverse grinding.